THE EFFECTIVENESS OF VIDEO MEDIA ON LEARNING OUTCOMESCLASS VII STYLE MATERIAL - Arinna, Oktaffi; Fauzyah, Emy (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
Media is the most important thing in the success of the learning process. Video media is very liked by students because learning becomes fun. But there are advantages and disadvantages in using video media in class. Style material is material with many abstract concepts so that media is needed to facilitate learning concepts including videos. This study aims to determine the effect of video media on student learning outcomes at SMP A. Wahid Hasyim Tebuireng. The sample in this study was class VII – I students as the control class and students in class VII – D as the experimental class with 31 students each. Data collection was obtained by random method. This study used a quasi-experimental study with a pretest-posttest control group design. The collected data were analyzed in the form of descriptive statistics. The results showed that the cognitive learning outcomes of students using power point media were in the moderate category. The learning outcomes of students using learning video media show a high category. Keywords: Video Media, Learning Outcomes, Style